Conversation between skin microbiota and the host: from early life to adulthood - Jimin Cha; Tae-Gyun Kim; Ji-Hwan Ryu (Experimental and Molecular Medicine)
Abstract Host life is inextricably linked to commensal microbiota, which play a crucial role in maintaining homeostasis and immune activation. A diverse array of commensal microbiota on the skin interacts with the host, influencing the skin physiology in various ways. Early-life exposure to commensal microbiota has long-lasting effects, and disruption of the epidermal barrier or transient exposure to these microorganisms can lead to skin dysbiosis and inflammation. Several commensal skin microbiota have the potential to function as either commensals or pathogens, both influencing and being influenced by the pathogenesis of skin inflammatory diseases. Here we explore the impact of various commensal skin microbiota on the host and elucidate the interactions between skin microbiota and host systems. A deeper understanding of these interactions may open new avenues for developing effective strategies to address skin diseases.